The Relationship Between Learning Interest and Cognitive Learning Outcomes of SMP N 21 Semarang Students: - - Ipah Budi Minarti; Nuke Hawarizqi; Roch Mayang Mekar (Sean Institute, 2023)
Abstract Learning interest has a very big influence on learning outcomes because if the subjects studied are not by students' interests, students will not study well because they feel not interested. Interest in learning has a positive and significant effect on learning outcomes. The purpose of this study is to determine the relationship between students' interest in learning and the cognitive learning outcomes of students at SMP N 21 Semarang. Data collection on learning interest and cognitive learning outcomes of students was taken from class VIII G. The method used was purposive sampling area and the data collection method used was observation and questionnaire. The result is that student's interest in learning in class VIII G is in the high category with an average of 76.76%. While the cognitive learning outcomes of students in class VIII G on the human respiratory system material are also included in the high category of 75.72% because they have fulfilled the KKM. Based on these results it can be concluded that there is a relationship between learning interest and cognitive learning outcomes of students at SMP N 21 Semarang.